II—Self-Awareness and Korsgaard's Naturalistic Explanation of the Good. (4th June 2018) - Rowlands, Mark
Abstract: This paper explores certain facets of Christine Korsgaard's paper, 'Prospects for a Naturalistic Explanation of the Good' (2018). Korsgaard's account requires that an animal be able to experience 'herself trying to get or avoid something'. The claim that animals possess such self-awareness is regarded by many as problematic and, if this is correct, it would jeopardize Korsgaard's account. This paper argues that animals can, in fact, be aware of themselves in the way required by Korsgaard's account.